21 Abnormal white-matter rich-club organization in obsessive-compulsive disorder. Issue 12 (14th November 2022) - Baldi, Samantha; Michielse, Stijn; Vriend, Chris; van den Heuvel, Martijn P; van den Heuvel, Odile A; Schruers, Koen RJ; Goossens, Liesbet
Abstract : Objectives: Although the exact neurobiology of obsessive-compulsive disorder (OCD) remains elusive, it has long been recognized that looking at brain networks is key. Graph theoretical analyses have proven valuable to understanding how information is integrated and communicated throughout a complex network. Key players in this process are network hubs, regions densely interconnected with each other forming a 'rich-club' within the brain, necessary for efficient communication between distant and/or segregated regions of the network. 1 Alterations in rich-club organization interfere with higher-order cognitive processes, and are common to several psychiatric and neurological conditions. A few studies examining the structural connectome in OCD suggest lower efficiency of information transfer across the brain. 2–4 The present study adds to the discussion and investigates rich-club organization and rich-club connectivity as potential markers of OCD, while including the preliminary analyses of a sample of unaffected first-degree relatives, with the aim of prompting further research into familial vulnerability. Methods: The structural connectome of 28 unmedicated OCD patients, 8 of their unaffected siblings and 28 healthy controls was reconstructed using diffusion-weighted imaging and probabilistic tractography. Following established methods, 1 topological and weighted measures of rich-club organization and connectivity were computed. Rich-club regions were selected as the top 16% most highly connected regions displaying rich-club organization at the group level. Global and local measures of network integration (efficiency) and segregation (clustering coefficient) were calculated alongside. Results: Compared to healthy controls, OCD patients displayed significantly lower topological and weighted rich-club organization, allocating a smaller fraction of all connection weights to the rich-club core. Consistent with previous reports, regions selected at the top 16% rich-club level included the bilateral precuneus, inferior parietal lobule, insula, cingulate gyrus, superior temporal lobe, fusiform gyrus, occipital cortex and, subcortically, bilateral hippocampus, thalamus, caudate and putamen. Global clustering coefficient, local efficiency and clustering of non-rich club nodes were significantly higher in OCD patients. Significant three-group differences emerged, with siblings displaying highest and lowest (never intermediate) values in different measures. Conclusions: Our results suggest weaker structural connectivity between rich-club regions in OCD patients, possibly resulting in lower network integration in favor of higher network segregation. We highlight the need of looking at network-based alterations in brain organization and function when investigating the neurobiological basis of this disorder, and stimulate further research into potential familial protective factors against the development of OCD. References: van den Heuvel MP, Kahn RS, Goni J, Sporns O. High-cost, high-capacity backbone for global brain communication. Proceedings of the National Academy of Sciences 2012;109 :11372–11377. doi:10.1073/pnas.1203593109 Zhong Z, Zhao T, Luo J, Guo Z, Guo M, Li P, Sun J, He Y, Li Z. Abnormal topological organization in white matter structural networks revealed by diffusion tensor tractography in unmedicated patients with obsessive-compulsive disorder. Progress in Neuro-Psychopharmacology and Biological Psychiatry 2014;51 :39–50. doi:10.1016/j.pnpbp.2014.01.005 Reess TJ, Rus OG, Schmidt R, de Reus MA, Zaudig M, Wagner G, Zimmer C, van den Heuvel MP, Koch K. Connectomics-based structural network alterations in obsessive-compulsive disorder. Translational Psychiatry 2016;6. doi:10.1038/tp.2016.163 Peng Z, Yang X, Xu C, Wu X, Yang Q, Wei Z, Zhou Z, Verguts T, Chen Q. Aberrant rich club organization in patients with obsessive-compulsive disorder and their unaffected first-degree relatives. NeuroImage: Clinical 2021;32 :102808.